(untitled) (Docentes 2.0 Journal, 2021)
The academic article described below is the underlying work of an investigative process aimed at analyzing the incidence of Novak’s theory in the learning of disciplinary concepts of the subject Economic History of Colombia in students of the 4th semester of the Economics program of the University of Pamplona, ??Colombia, the study is of mixed approach, where in order to achieve the established objective, an identification process was carried out in accordance with the learning of disciplinary concepts in the students under study. Likewise, as instruments for collecting information, a diagnostic test by competencies, an aptitude test and a final interview were applied, results with which it was possible to establish the impact and incidence of concept maps in the teaching of disciplinary concepts of Economics. The results obtained show the importance of incorporating tools such as concept maps for teaching theoretical content, where it is necessary for teachers to adapt their pedagogical methods to the learning needs of their students, seeking not only the teaching content in a mechanical way, but rather generating in them enough intrinsic motivation that allows them to acquire skills so that they can build meaningful quality learning, according to the economic demands that are presented in today’s world.